INTEGRITAS DAN TANGGUNG JAWAB ULAMA DALAM ISLAM: TELAAH RESEPSI MAMA SEMPUR DALAM KITAB IHYA’UL-MAYYIT - ade kosasih (PT. RANESS MEDIA RANCAGE, 2025)
Muslim scholars or intellectuals are important figures who play a very strategic role in Islamic society. They not only serve as spiritual and religious guides but also as the main pillars in preserving and developing religious and moral values in society. In reality, some Muslim scholars and religious leaders are also caught up in worldly pragmatism, so their role as successors to the prophets is not reflected in their personalities. The noble role of religious leaders is sometimes ignored or even betrayed, causing the authority and exemplary nature of religious leaders and Muslim scholars to fade among Muslims. The general public experiences a void in terms of exemplary behaviours in rituals, social, spiritual, and cultural matters. This study aims to reveal the role and function of Muslim scholars and intellectuals in carrying out their noble duties of scholarship and intellectualism. One figure who always reminds us of the function, role, and responsibility of scholars in this life is Mama Sempur, a scholar who is highly respected among his followers and who gives advice in his religious study activities. Mama Sempur is widely known for his dedication to spreading the teachings of Islam with sincerity and patience, especially to his students and disciples. Through various effective teaching methods, he not only transfers religious knowledge theoretically but also teaches how to implement Islamic values in life and this world. One of his teachings is written in his work titled Ihyâ`ul-mayyit. The intertextual method is used to uncover the social role of scholars found in the texts of Mama Sempur's works. In this work, Mama Sempur highlights two important aspects for scholars or intellectuals: the scholars' duty as a responsibility and the threat faced by scholars who conceal the truth.